1991
DOI: 10.1007/bf00370797
|View full text |Cite
|
Sign up to set email alerts
|

Antidromic vasodilation in frog: identification of the nerve fiber types involved

Abstract: In anesthetized, immobilized frogs arteriolar vasodilation in the submaxillaris muscle in response to electrical stimulation of the submaxillar nerve (peripheral end) was observed directly and vasodilation in the hind leg in response to stimulation of the sciatic nerve (peripheral end) measured by plethysmography. With pulses of 0.1 ms duration at 20 Hz, the threshold for arteriolar vasodilation in the submaxillaris muscle was close to 3 T, where T was the activation threshold of the most excitable fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Later studies confirmed the existence of cholinergic neurogenic vasodilation in the frog microcirculation (Siggins and Weitsen, 1971) and the hypothesis of neurally-mediated spreading vasodilation persisted for many years. Indeed, ensuing work in the frog concluded that antidromic vasodilation arising from hindleg skeletal muscle was mediated by activating fine myelinated nerve fibers (Khayutin et al, 1991). During this period, alternative explanations were evolving in other laboratories using different experimental approaches to explain the ability of vasodilator signals originating within the distal microcirculation to encompass the proximal arterial supply (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Later studies confirmed the existence of cholinergic neurogenic vasodilation in the frog microcirculation (Siggins and Weitsen, 1971) and the hypothesis of neurally-mediated spreading vasodilation persisted for many years. Indeed, ensuing work in the frog concluded that antidromic vasodilation arising from hindleg skeletal muscle was mediated by activating fine myelinated nerve fibers (Khayutin et al, 1991). During this period, alternative explanations were evolving in other laboratories using different experimental approaches to explain the ability of vasodilator signals originating within the distal microcirculation to encompass the proximal arterial supply (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Antidromic vasodilatation is most obvious when electrical stimulation is strong enough to recruit unmyelinated (C) fibres (Hinsey and Gasser 1930;Low and Westerman 1989;Koltzenburg et al 1990) which are connected to nociceptors (Celander and Folkow 1953a;Blumberg and Wallin 1987;Magerl et al 1987), but it has recently been shown that also some thin myelinated (AS) fibres can give rise to cutaneous hyperaemia (Lynn 1988;J~rtig und Lisney 1989). In frogs only A8 fibres are able to induce antidromic vasodilatation (Khayutin et al 1991). The magnitude of hyperaemia depends on the number and frequency of the stimuli delivered to the nerve (Celander and Folkow 1953b;Magerl et al 1987;Szolcs~inyi 1988;J~inig and Lisney 1989), yet only one or two impulses or a frequency of 0.025 Hz are sufficient to elicit some vasodilatation as detected by laser Doppler velocimetry (Magerl et al 1987;Lynn 1988;Lynn and Shakhanbeh 1988a;Szolcs~inyi 1988;Scolcs~inyi et al 1992).…”
Section: Nature Of Afferent Vasodilator Fibresmentioning
confidence: 99%